Heidegger and the Obliteration of Language: For a Critique of Linguistic Theory or General Linguistics - Moreno Tirado, Guillermo (2024)
This paper discusses the grounding of the possibility of a critique of general linguistics or linguistic theory based on an interpretation of a passage of Heidegger’s Letter on Humanism. According to my interpretation, the metaphysical conception of language generates an obliteration that does not allow to understand the phenomenon of language or languages. However, I claim that such a conception and, therefore, the obliteration itself are part of the phenomenon of language and not something external that can be avoided. Therefore, I raise the question if linguistics supports such a conception and defend that the obliteration diagnosed by Heidegger requires a discrimination of the fundamental concepts of linguistics and its presuppositions. I suggest as a work hypothesis in the context of critical practice that it is not linguistics itself that supports this conception –such as it is observable after the discrimination of its fundamental concepts– but rather its presuppositions. Consequently, I claim that the fundamental concepts of linguistics –when critically considered– deconstruct the presuppositions according to which linguistic theory conceives language and its own theoretical grounding.